2009
DOI: 10.20450/mjcce.2009.225
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and recycling of polymer eco-composites I. comparison of the conventional molding techniques for preparation of polymer eco-composites

Abstract: The interest in natural fiber-reinforced polymer composites is growing rapidly due to their high performance in terms of mechanical properties, significant processing advantages, excellent chemical resistance, low cost and low density. In this study, the compression and injection molding of polypropylene (PP) and polylactic acid (PLA) based composites reinforced with rice hulls or kenaf fibers was carried out and their basic properties were examined. Rice hulls from rice processing plants and natural lignocell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Moreover, a high degree of bending and buckling was observed in other types of developed composites. Improvement in compressive strength of biocomposites was also reported earlier, [40][41][42][43] which showed that compressive strength greatly depends upon size and type of natural fibers.…”
Section: Compressive Testsupporting
confidence: 77%
“…Moreover, a high degree of bending and buckling was observed in other types of developed composites. Improvement in compressive strength of biocomposites was also reported earlier, [40][41][42][43] which showed that compressive strength greatly depends upon size and type of natural fibers.…”
Section: Compressive Testsupporting
confidence: 77%
“…Our previous results on kenaf fiber/PLA composites have shown that their mechanical properties are comparable to those of conventional formaldehyde wood medium-density fiberboards used as construction elements for indoor applications [12]. Moreover, it was confirmed that both conventional injection and compression molding techniques could be successfully applied for their production.…”
Section: Resultsmentioning
confidence: 53%
“…Their mechanical properties are comparable to those of E-glass fibers (Table 1) [11]. In our previous work [12], we investigated the characteristics of PLA/kenaf fiber composites processed by compression and injection molding, and the obtained results have shown that the overall mechanical properties are comparable to those of conventional formaldehyde wood mediumdensity fiberboards used as construction elements for indoor applications.…”
Section: Introductionmentioning
confidence: 78%
“…The beneficial effects of maleic anhydride on polymer composites’ compatibility were repeatedly reported in the literature, both for lignocellulose [ 74 , 75 ] and mineral [ 76 ] fillers. Such an effect is associated with the partial “crosslinking” of material due to generation of covalent bonds [ 77 ].…”
Section: Resultsmentioning
confidence: 69%